2019
DOI: 10.1108/ijem-09-2017-0237
|View full text |Cite
|
Sign up to set email alerts
|

A minimalist design for distance learning

Abstract: Purpose The purpose of this paper is to determine whether the application of the minimalist approach is appropriate in distance learning (DL). Design/methodology/approach A survey of faculty who have participated in DL training courses at a university in the southeastern USA was conducted. In total, 72 faculty completed the survey, for a response rate of 34 percent. Findings Survey research findings demonstrate support for the suitableness of a minimalist approach to DL, as results indicate that faculty me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…During the COVID-19 pandemic, laptops and smartphones have been primary devices for lecturers and students in EdTech low-resourced African universities to stay in touch and engage meaningfully during online lessons [ 10 ]. In education systems with low EdTech resources, online teaching and learning should only provide significant and demonstrable benefits to students [ 10 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic, laptops and smartphones have been primary devices for lecturers and students in EdTech low-resourced African universities to stay in touch and engage meaningfully during online lessons [ 10 ]. In education systems with low EdTech resources, online teaching and learning should only provide significant and demonstrable benefits to students [ 10 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minimalism is all about finding the essentials in life. Minimalists’ theories argue that online instruction should only include that which provides significant and demonstrable benefits to a student’s course [ 10 , 35 ]. Instructors and learners do not require several sophisticated gadgets and software resources to have a successful online lesson but minimal essential ICT tools and software in the public domain.…”
Section: Theorisation: Online Instruction Through a Minimalist Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…An article by Carraher Wolverton, C., & Guidry Hollier, B. provides an answer to the question of whether a minimalist approach is appropriate in distance learning. The results show that less technology should be used, the training required to teach an online course (Carraher Wolverton, & Guidry Hollier, 2019 (Gegenfurtner, & Ebner, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…However, Bolliger and Wasilik (2009) indicated that online instruction is a complex undertaking and requires a higher level of commitment from faculty. Many instructors, whether they have taught online courses or not, feel that they did not enjoy it as much as teaching face-to-face classes (Carraher Wolverton and Guidry Hollier, 2019).…”
Section: Introductionmentioning
confidence: 99%